Aplikasi Diagnosa Penyakit Gigi dan Pengobatannya Menggunakan Metode Forward Chaining dan Association Rule Analysis - Andi Muh. Lukman (JTRISTE, 2016)
Patients with dental disease can also be affected by another, suffered from dental disease, as based on medical science, dental disease may spread and can cause organs of the body experiencing pain. It is of course also have a way of handling, namely to diagnose whether the disease suffered by the patient's teeth may propagate or not based on the characteristics that are applicable to the theory of the medical science. Data collection techniques used include observation, interview, and literature study. For data analysis techniques using methods Forward Chaining. Part Base testing as an alternative to white box testing, the authors use the method Basis Path Testing, inputting the data symptom / disease diagnosis to be made a rule to the knowladge base. Where inputting is done by the experts at the General Hospital Makassar Power. Based on the results of the use of forward chaining method and association rule analysis, we can conclude that the information about the symptoms that cause dental disease and its treatment in the form of action or treatment.